Enterococcus gallinarum Spontaneous Bacterial Peritonitis in an HCV Cirrhotic - Hussein Abidali; Maheen Sheikh; Moustapha Abidali; Ali Abidali; Hamoudi S. Farraji; Andrew C. Berry (Case Reports in Hepatology)
We present the case of a 60-year-old Caucasian male with history of hepatitis C viral cirrhosis with portosystemic encephalopathy and ascites with evidence of spontaneous bacterial peritonitis (SBP) with absolute neutrophil count (ANC) of 944 cells/µL blood. Despite adequate treatment, the abdominal pain and elevated creatinine continued to persist. Initial ascites fluid cultures returned back positive for growth of Enterococcus gallinarum. Empiric antibiotics were then substituted with ampicillin/sulbactam. Our case of Enterococcus gallinarum causing SBP is only the seventh case reported in the literature to date.